Kapabilitas Influencer Marketing dan Content Marketing dalam Industri Pariwisata Magelang terhadap Keterlibatan Pelanggan dengan Viral Marketing sebagai Variabel Intervening di Era 5.0 - Setya Indah Isnawati; Eko Nur Hermansyah; Adi Purwanto (Journal of Economics and Management Scienties, 2026)
The rapid increase in TikTok users until 2025 has encouraged tourism industry players in Magelang Regency to adopt more interactive and viral communication strategies to build closeness with consumers. This study aims to examine the effect of influencer marketing and content marketing on customer engagement with viral marketing as a mediating variable in the tourism industry in Magelang Regency. This study uses quantitative methods and PLS-based Structural Equation Modeling (SEM). Data were collected through questionnaires from 230 tourists in five tourist destinations in Magelang Regency, which were selected using convenience sampling. The analysis was conducted using PLS software to confirm the suitability of the empirical model and the relationship between the research variables. The results show that both digital marketing strategies have a positive and significant effect on customer engagement, both directly and through viral marketing. Viral marketing has been proven to be a mediator that strengthens the relationship between digital marketing strategies and customer engagement. The research model explains 61% of the variability in customer engagement, confirming that content virality is a strategic mechanism in enhancing the effectiveness of digital marketing in the 5.0 era. These findings imply that optimizing influencer collaboration and content quality is crucial for driving sustainable tourist engagement.